Manajemen Sumber Daya Manusia Islami - Syamsul; Adi Muh Arman; Rika Dwi Ayu Parmitasari; Alim Syariati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Human Resource Management is a field of management that specifically studies the relationship and role of humans in organizations and companies. Competition in the work environment is one of the main factors in the expansion of the role and importance of the human resource management function in organizations and companies. Management that the majority of people understand is management with a conventional system. But lately, with the development of the Islamic economy raises a new phenomenon, especially on the side of practitioners or human resources. The development of Islamic economic practices in Indonesia is growing day by day, it is marked by the growth and development of financing Islamic financial institutions and real sector activities that use Islamic economic principles. So, it is necessary to know whether organizations and companies that use the label of Islamic economics have also implemented management management based on Islamic values based on the Koran and Hadith.